Young Women’s Reception of Infidelity Representation in the Film Ipar Adalah Maut: A Stuart Hall Reception Analysis - Novita Firnanda Sari; Agus Triyono (LPPM STIAB JINARAKKHITA LAMPUNG, 2026)
Films have evolved beyond entertainment into spaces where audiences construct and negotiate meanings about contemporary social issues. This study examines how young women interpret the representation of infidelity in the film through Stuart Hall’s Reception Theory. Employing a descriptive qualitative approach, the study combines in-depth interviews with netnographic observation to capture both individual interpretations andaudi ence interactions within digital environments. A key novelty of this study lies in integrating in-depth interviews and netnographic observation, enabling audience reception to be examined across both personal interpretations and participatory digital discussions. Eight female participants aged 18–25 years who had watched the film and actively used social media were selected through purposive sampling. Data were analyzed using Hall’s encoding–decoding framework by classifying audience interpretations into dominant, negotiated, and oppositional reading positions. The findings indicate that most participants occupied the dominant reading position by accepting the film’s portrayal of infidelity as a violation of trust, commitment, and family values, while a smaller number demonstrated negotiated readings by incorporating personal experiences and social contexts into their interpretations. No oppositional reading was identified, suggesting a strong alignment between the film’s preferred meanings and participant’s moral and cultural values. The study contributes to audience reception research by demonstrating how media meanings are shaped through the interaction of cultural values, personal experiences, and participatory digital practices, while extending Hall’s Reception Theory to contemporary digital communication environments.